BAHASA JAWA SEBAGAI IDENTITAS GENERASI MUDA MASYARAKAT PENDATANG DARI JAWA DI MERAUKE - Hanova Rani Eka Retnaningtyas (Universitas Sebelas Maret, 2023)
The Javanese ethnic community is widespread throughout the archipelago, although it is not well-known as an ethnic group that likes to wander. One of the places that later became the new residence of this ethnic group was the city of Merauke in Papua. The area at the easternmost tip of Indonesia. Far from the area of origin and have never even been to the island of Java, it is common for the Javanese people who live in Merauke to live. This can be a factor causing the weakening of the